One-ton stone: how rock 'n' roll became heaviness: how rock 'n' roll became heavy (Orfeu, 2023)
The present article presents a bibliographical research, within the field of study of musical genres, about the development of what is conventionally called “heaviness” sound over approximately seven decades of rock history, which in its origin did not have such a characteristic of sound aesthetics – although there were already its beginnings, with the saturation caused by the use of high amplitude in low-power amplifiers in the late 1940s and early 1950s – but which gradually became evident over time, becoming a constant concern of many musicians or even a defining feature of several rock subgenres.
Keywords: heaviness; heavy music; rock; electric guitar; saturation